Karakter Islami dalam Perspektif Filsafat Pendidikan di MI Slubung Blitar - Efendi, Mohamad Yusuf; Basiran, Basiran (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the Islamic character at MI Slubung Blitar and Islamic character from the perspective of educational philosophy at MI Slubung Blitar. So this research raises the title